IMPLEMENTATION OF INTEGRATED ADMINISTRATIVE SERVICES BASED ON GOOD GOVERNANCE AT THE OFFICE OF BATUDAA SUB-DISTRICT OFFICE - Macmud, Joyce; Lamangida, Trisusanti (Universitas Negeri Gorontalo, 2022)
The study is done at the sub-district office of Batudaa Gorontalo, the purpose of this study is to find the administration based integrated good governance in Batudaa sub-district office. The methodology from the analysis qualitative baseline data, from interviews informants, and direct observation in the field. The result showed that, the implementation of public service good governance based at sub-district office of Batudaa Gorontalo referring to the Gorontalo regent number 28 years 2014 about the delegation part of their authority to head the in the program integrated administration services in (PATEN). The authority has delegate to district in order to public services in Batudaa: district includes a) service the field of licensing; and b) service non-permission sector. But for the implementation of public services, based on ministerial regulation no 4 years 2010 and guidance technical integrated administration services in, been implemented principles terra (tangibles, empathy, reliability, responsive and assurance).